La pintura francesa en los primeros años de La Ilustración Española y Americana (1870-1880) - Lola Bermúdez Medina (Cahiers de Civilisation Espagnole Contemporaine)
La Ilustración Española y Americana (1869-1921), a follow-up to the Museo Universal, was one of Spain’s most renowned journals at the end of the 19th century –its prestige based on its high-quality illustrations as well as its famous contributors. Through its pages it effectively spreads European developments in the arts, society, politics and culture throughout the Spanish-speaking world. This paper is an account of the presence of French painting during the first ten years of the journal’s life. In keeping with the journal’s overall orientation, the approach to French painting is politically conservative, so much so that during this period no mention is made of burgeoning Impressionism.